Assessment of knowledge concerning prevention of infection with HCV among nurses employed in surgical wards - Sierpińska, Lidia; Wójcik, Olga (Journal of Education, Health and Sport, 2025)
Background and study aims. Infection with hepatitis C virus (HCV) may lead to acute or chronic hepatitis. About 3% of the world's population is infected, while in Poland approximately 2%. Occupational exposure among nurses is related with the provision of care to patients in surgical wards which are an important source of infection with HCV. The aim of the study was assessment of the level of knowledge concerning prevention of HCV infection among nurses employed in surgical wards. Materials and Method. The study included 148 nurses working in surgical wards in Polish hospitals, and was conducted by the method of a diagnostic survey, using an author-constructed questionnaire and a modified questionnaire designed by the Polish HCV Expert Group. Results. The majority of nurses in the study had a mediocre level of knowledge concerning hospital-acquired infections transmitted through blood, methods of prevention of hospital-acquired infections with HCV, and methods of protection against occupational exposure to HCV infection. The majority of respondents provided correct answers regarding the risk of infection with HCV. The deficit of respondents’ knowledge concerned the lack of vaccine against hepatitis C and the possibility of curing a person infected with HCV as long as the disease is diagnosed early. Conclusions. Nurses employed in surgical wards should be motivated to expand their knowledge concerning prevention of HCV infections. Training courses should include the methods of prevention of infections with HCV, ways to protect against occupational exposure to HCV infection, and the possibilities of treatment of persons infected with HCV.